LncRNA XLOC013218 promotes cell proliferation and TMZ resistance by targeting the PIK3R2‐mediated PI3K/AKT pathway in glioma. Issue 8 (14th June 2022) - Zhou, Jian; Xu, Ningbo; Liu, Boyang; Wang, Chenyang; He, Zhenyan; Lenahan, Cameron; Tang, Wenhui; Zeng, Huijun; Guo, Hongbo
Abstract: The discovery of long noncoding RNAs (lncRNAs) has improved the understanding of development and progression in various cancer subtypes. However, the role of lncRNAs in temozolomide (TMZ) resistance in glioblastoma multiforme (GBM) remains largely undefined. In this present study, the differential expression of lncRNAs was identified between U87 and U87 TMZ‐resistant (TR) cells. lncRNA XLOC013218 (XLOC) was drastically upregulated in TR cells and was associated with poor prognosis in glioma. Overexpression of XLOC markedly increased TMZ resistance, promoted proliferation, and inhibited apoptosis in vitro and in vivo. In addition, RNA‐seq analysis and gain‐of‐function or loss‐of‐function studies revealed that PIK3R2 was the potential target of XLOC. Mechanistically, XLOC recruited specificity protein 1 (Sp1) transcription factor and promoted the binding of Sp1 to the promoters of PIK3R2, which elevated the expression of PIK3R2 in both mRNA and protein levels. Finally, PIK3R2‐mediated activation of the PI3K/AKT signaling pathway promoted TMZ resistance and cell proliferation, but inhibited cell apoptosis. In conclusion, these data highlight the vital role of the XLOC/Sp1/PIK3R2/PI3K/AKT axis in GBM TMZ resistance. Abstract : lncRNA XLOC013218 (XLOC) confers temozolomide (TMZ) resistance of glioma by promoting cell proliferation and inhibiting cell apoptosis via activation of the PIK3R2‐mediated PI3K/AKT signaling pathway in an Sp1‐dependent manner.